The influence of participatory assistance and organizational culture on strengthening social capital of Buddhist cooperative - Rahmad Setyoko (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP) Sekolah Tinggi Ilmu Agama Buddha Smaratungga, 2021)
The social capital of an organization strengthens mutually beneficial cooperation to achieve common goals. This research aims to analyze the influence of participatory assistance and organizational culture on strengthening the Buddhist Cooperative's social capital. This research employs a quantitative approach with an ex post facto method. The sample was 77 members of Cooperative Maju Makmur Sampetan, and data were collected by using a questionnaire. Findings show that participatory assistance and organizational culture significantly influence strengthening the social capital of Buddhist Cooperative. Based on the regression analysis, it shows that there is a positive and significant influence of participatory assistance on social capital, which is equal to 44.5%. Organizational culture also has a positive and significant influence on social capital, with a determination of 32.1%. Furthermore, multiple regression analysis results show that both variables simultaneously influence strengthening social capital, with the coefficient of determination by 76.6%. Thus, participatory assistance and organizational culture have a positive effect on strengthening social capital of Buddhist Cooperative.